Corneal Ulcers Treatment - Farida, Yusi (Majority, 2015)
Abstract Extensive corneal ulcers require precise handling and fast for the prevention of the onset of complications such as descementocele, perforation, endophthalmitis and blindness. Corneal ulcers that heal will cause cloudiness of the cornea and leading the second cause of blindness in Indonesia. The purpose of eradication treatment of corneal ulcers are eradication of the corneal ulcer, suppress inflammatory reactions so as not to aggravate the destruction of the cornea, accelerate healing epithelial defects, predominate the complications and improve visual acuity. This can be done by giving appropriate and prompt treatment according to culture and sensitivity test results causing microorganisms. Prognosis of corneal ulcers depends on the severity and rapid than get help, the type of microorganism causes and the presence or absence of complications arising. Management of corneal ulcers are not limited to providing antimicrobial, but the general state of repair as well as measures to ease the symptoms and eliminate the cause. Some of the causes of corneal ulcers include foreign bodies and contact lenses. Keywords: Corneal, causes, treatment, ulcers. Abstrak Ulkus kornea yang luas memerlukan penanganan yang tepat dan cepat untuk mencegah perluasan ulkus dan timbulnya komplikasi seperti descementocele, perforasi, endoftalmitis, bahkan kebutaan. Ulkus kornea yang sembuh akan menimbulkan kekeruhan kornea dan merupakan penyebab kebutaan nomor dua di Indonesia. Tujuan penatalaksanaan ulkus kornea adalah eradikasi penyebab dari ulkus kornea, menekan reaksi peradangan sehingga tidak memperberat destruksi pada kornea, mempercepat penyembuhan defek epitel, mengatasi komplikasi serta memperbaiki tajam penglihatan. Hal tersebut dapat dilakukan dengan pemberian terapi yang tepat dan cepat sesuai dengan kultur serta hasil uji sensitivitas mikroorganisme penyebab. Prognosis ulkus kornea tergantung pada tingkat keparahan dan cepat lambatnya mendapat pertolongan, jenis mikroorganisme penyebabnya, dan ada tidaknya komplikasi yang timbul. Penatalaksanaan ulkus kornea tidak terbatas pada pemberian anti mikroba, melainkan perbaikan keadaan umum, serta tindakan-tindakan untuk memperingan gejala dan menghilangkan penyebab. Beberapa penyebab ulkus kornea antara lain adalah benda asing dan lensa kontak. Kata kunci: Kornea, penatalaksanaan, penyebab, ulkus